Determinants of Firm Value in Indonesia Consumer Non-Cyclical Companies: Perspectives of Environmental Performance, Board Diversity, and Earnings Quality - Rahmadani Sandrigus Shanon; Rizdina Azmiyanti (BIP's JURNAL BISNIS PERSPEKTIF, 2026)
The objective of this study is to examine and analyze the effects of environmental performance, board age diversity, board gender diversity, and earnings quality on firm value among companies in the non-cyclical consumer sector listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. This study employs a quantitative method using secondary data. The study population consists of 132 companies, and purposive sampling was used to determine the sample, resulting in 75 data points. The research method employs panel data regression using EViews 13 software. The results demonstrate that environmental performance and board gender diversity do not influence firm value, whereas board age diversity can reduce firm value, and the magnitude of earnings quality can increase firm value. It is expected that this study will serve as a consideration for management and investors, as well as a reference for future research to examine the factors that influence firm value